Pengabdian Masyarakat melalui Teknologi Osama Biobased Economy untuk Budidaya Cabai di Desa Sukasari Kabupaten Tasikmalaya - Egi Nuryadin; Ika Rahmawati; Fitri Natalia; Maya Cindiati; Dina Husnul Khotimah; Annisa Choerunnisa (Institut Pertanian Bogor, 2022)
Chili is one of the important food ingredients. The lack of public knowledge about chili cultivation techniques and good land optimization makes people's interest to grow chili less. In addition, household organic waste management in Tasikmalaya, especially in Sukasari Village, has not been optimal. The objectives of this service activity are 1) To provide knowledge and skills about chili cultivation techniques; 2) Utilization of household organic waste through the technology of processing household organic waste into organic fertilizer that can have economic value (Osama biobased economy); and 3) Educate the public regarding the optimization of yard land. The partners in this activity are the Jaya Mukti Farmers Association and Mukti Farmers Group which are located in adjacent areas with a total of 32 people using a random sampling technique because the sample is homogeneous. The activities carried out were in the form of socialization, demonstration, and practicum on household organic waste processing technology (Osama), chili cultivation techniques and optimization of yard land, as well as distribution of seeds and fertilizers to the community. The data collection technique in this activity uses a questionnaire. The results of this service activity indicate that there is an increase in community knowledge and skills in chili cultivation and the use of household organic waste and home yards.